Mutu Pelayanan Puskesmas dengan Status Akreditasi di Puskesmas - Duha, Sonya Marsela Pieta; Ginting, Chrismis Novalinda; Nasution, Ali Napiah (Journal of Telenursing (JOTING), 2024)
This study aimed to see the relationship between service quality and the accreditation status of the Health Center. The research method used a cross-sectional study. Data were collected using a questionnaire sheet. The collected data were analyzed using the Chi-Square test. The study's results showed a significant relationship between the service quality dimensions (responsiveness, assurance, tangible, empathy, and reliability) and the accreditation status of the health center. This study concludes a relationship between responsiveness, assurance, tangible, empathy, and reliability with accreditation status. Keywords: Accreditation, Service Quality, Health Center